2018
DOI: 10.1002/lno.10954
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial support of zooplankton biomass in northern rivers

Abstract: The contribution of terrestrially derived carbon to micro‐crustacean zooplankton biomass (i.e., allochthony) has been previously studied in lakes, reservoirs, and estuaries, but little is known about zooplankton allochthony in rivers. In lacustrine environments, allochthony is regulated by distinct selective feeding behavior of different taxa. However, we hypothesized that restricted possibility for selective grazing in turbulent environments such as rivers would decouple zooplankton from specific microbial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
(98 reference statements)
1
5
0
Order By: Relevance
“…Numerous studies have demonstrated a positive relationship between inflows, terrestrial carbon assimilation and the growth of juvenile fish in estuaries, attributing this to increased prey resources following inflows [8,9,26,60]. Our results provide potential support to the notion that terrestrial carbon uptake by zooplankton after inflows [19,20,22] can positively influence the somatic growth of juvenile fish, providing increased energetic resources. However, there were relatively small changes in juvenile size within our experiment, both between treatments and across the experimental timeframe, and only minor changes in isotopic ratios of fish tissue.…”
Section: Tdom Inflows and Juvenile Fishsupporting
confidence: 80%
See 2 more Smart Citations
“…Numerous studies have demonstrated a positive relationship between inflows, terrestrial carbon assimilation and the growth of juvenile fish in estuaries, attributing this to increased prey resources following inflows [8,9,26,60]. Our results provide potential support to the notion that terrestrial carbon uptake by zooplankton after inflows [19,20,22] can positively influence the somatic growth of juvenile fish, providing increased energetic resources. However, there were relatively small changes in juvenile size within our experiment, both between treatments and across the experimental timeframe, and only minor changes in isotopic ratios of fish tissue.…”
Section: Tdom Inflows and Juvenile Fishsupporting
confidence: 80%
“…All filter papers were placed into plastic bags and then frozen (−14 • C). The frozen fish were dried at 50 • C for 96 h, crushed to homogenise the tissue and stored at -20 • C. POM, Artemia and homogenised fish material were analysed for stable isotope ratios of carbon (δ13C) and nitrogen (δ15N) using a continuous flow-isotope mass spectrometer (GV IsoprimeEurovector EA 3000, Manchester, UK) and a Sercon Hydra [20][21][22] stable isotope ratio mass spectrometer, respectively. The results were determined against laboratory standard reference material IAEA-CH-6 and atmospheric nitrogen.…”
Section: Pom and Tissue Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Terrestrial OM has long been considered an unimportant resource for pelagic aquatic food webs and has been often excluded from the calculations of carbon flux supporting primary and secondary consumers. Increased evidence of a significant share of zooplankton biomass having a terrestrial origin (i.e., allochthony; Emery et al , Cole et al , Pace et al , Berggren et al ), questions this view of t‐OM as an unimportant food source. However, as t‐OM lacks essential elements for growth (Taipale et al ), the high abundance of terrestrial carbon in zooplankton tissues is not expected to promote the production of consumer biomass, but rather to result in organisms having a reduced growth capacity (Brett et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a period with higher precipitation and freshwater inflow to the northern Baltic Sea (Gulf of Bothnia) was shown to result in reduced primary production, which further affected the benthic fauna negatively (Wikner and Andersson 2012;Eriksson-Wiklund and Andersson 2014). Inputs of terrestrial organic matter may indirectly favor the development of cyanobacteria, for example via co-transported nutrients (Stolte et al 2006), but both terrestrial organic matter and cyanobacteria are of low food quality for zooplankton (Guschina and Harwood 2009;Berggren et al 2018;Senar et al 2019). Browning can also promote the production of heterotrophic bacteria instead of phytoplankton, thereby enhancing the bacterial trophic pathway (bacteria-ciliatesheterotrophic flagellateszooplankton; Wikner and Andersson 2012).…”
Section: Introductionmentioning
confidence: 99%